Capturing ribosomal structures in cellular extracts with cryoPRISM: A purification-free cryoEM approach reveals novel structural states - Mira B. May; Gabriella S. Lopez-Perez; Joseph H. Davis (Proceedings of the National Academy of Sciences, 2026)
Structural analyses of ribosomes by single particle cryogenic electron microscopy (cryoEM) have traditionally relied on purified or reconstituted samples, with particles often trapped in desired states using genetic, pharmacological, or biochemical perturbations. While informative, such in vitro methods often fail to capture the full diversity of structural states and associated protein factors present in cells. In contrast, in situ cryoelectron tomography preserves cellular context but is limited by low throughput and modest resolution. Here, we present cryoPRISM (purification-free ribosome imaging from subcellular mixtures), a rapid ex vivo workflow encompassing cell lysis, vitrification, and image analysis methods for high-resolution analyses of ribosomal structures directly from cell lysates. Applying cryoPRISM in Escherichia coli , we resolved more than 20 distinct ribosomal states spanning assembly, translation initiation, elongation, trans-translation, and quiescence, including a novel configuration of EF-G bound to idle ribosomes with the ribosome hibernation factor ribosome-associated inhibitor A. Given its speed, accessibility, and ability to preserve native interactions and structural heterogeneity, we anticipate that cryoPRISM will be broadly applicable for uncovering ribosomal biology across diverse organisms and conditions.